Adverse maternal and fetal outcomes associated with traditional herbal medicine use in Sub-Saharan Africa: a systematic review - Muoka, Chibuzor G.; Moneke, Ijeoma I.; Ukandu, Soromtochukwu F.; Ofoegbu, Chinyere G.; Onubogu, Chiemela O.; Ngwogu, Chinedum D.; Nwamuo, Henry S.; Nnorom, Princess C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Traditional herbal medicine use is widespread during pregnancy in Sub-Saharan Africa (SSA), driven by cultural beliefs, limited access to healthcare, and affordability. Despite this, concerns persist about its safety, especially its impact on maternal and fetal outcomes. This systematic review synthesizes evidence on the adverse outcomes associated with herbal medicine use during pregnancy across SSA. A systematic literature search was conducted using PubMed, Google Scholar, African Journals Online (AJOL), and Scopus for studies published up to May 2025. Inclusion criteria comprised studies conducted in SSA involving pregnant women using herbal medicines with reported maternal and/or fetal outcomes. Observational studies, qualitative research, ethnobotanical surveys, and case reports were included. Study quality was assessed using the Joanna Briggs Institute (JBI) critical appraisal tools. A total of 23 studies met inclusion criteria and underwent narrative synthesis. Findings revealed a high prevalence of unsupervised herbal use across SSA. Reported adverse maternal outcomes included uterine rupture, preterm labor, postpartum hemorrhage, and increased cesarean delivery rates. Gastrointestinal and psychological side effects were also noted. Adverse fetal outcomes included stillbirth, early neonatal death, low birth weight, congenital anomalies, and low APGAR scores. Utero-tonic herbs such as Mwanamphepo and Kaligu-tim were commonly implicated. The majority of studies were of high methodological quality but often lacked precise herb identification and dosage standardization. This review highlights the significant health risks associated with traditional herbal medicine use during pregnancy in SSA. There is an urgent need for targeted public health education, clinician training, and stricter herbal medicine regulation to safeguard maternal and neonatal health.